Records management at the Council of Europe (1): three years of shock therapy. Issue 2 (1st August 2021) - Lisney, Tim
Abstract : While the Council of Europe as an Intergovernmental Organization has proven remarkably resilient, its archives and records appear to be increasingly fragile. This article documents and analyses the development of records management and archives management within the Council of Europe between 2000 and 2003. This was a period that saw major changes in the way that records were treated in the organization, notably the preparation and implementation of an organization-wide archives policy, and the introduction of an archives management training programme for Council of Europe staff. The concept of archives and records was extended from paper to electronic and audio-visual materials. An internal network of archive correspondents was introduced to increase communication, consultation, co-ordinate RM and facilitate the implementation of the archives policy, and a series of measures was taken to improve access to the archives and records. It was during this period that the first steps were taken in the introduction of archives and records management standards ISAD(G) and ISO 15489. The article highlights the lack of continuity of RM and the increasing vulnerability of records within the organization, suggesting that the lack of professional staff is the most critical issue; the analysis of the developments in this period also illustrates the impact that personal initiatives can have in such a context.